2018
DOI: 10.3390/polym10121400
|View full text |Cite
|
Sign up to set email alerts
|

Improved Physicochemical Stability and High Ion Transportation of Poly(Arylene Ether Sulfone) Blocks Containing a Fluorinated Hydrophobic Part for Anion Exchange Membrane Applications

Abstract: A series of anion exchange membranes composed of partially fluorinated poly(arylene ether sulfone)s (PAESs) multiblock copolymers bearing quaternary ammonium groups were synthesized with controlled lengths of the hydrophilic precursor and hydrophobic oligomer via direct polycondensation. The chloromethylation and quaternization proceeded well by optimizing the reaction conditions to improve hydroxide conductivity and physical stability, and the fabricated membranes were very flexible and transparent. Atomic fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…As shown in Figure , the activation energy ( E a ) of the prepared membranes was calculated by the Arrhenius equation, and the result showed a range between 6.86 and 11.41 kJ mol −1 . As a result, the E a of the membranes indicated that a vehicular mechanism was the main proton transport mechanism in all the membranes …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…As shown in Figure , the activation energy ( E a ) of the prepared membranes was calculated by the Arrhenius equation, and the result showed a range between 6.86 and 11.41 kJ mol −1 . As a result, the E a of the membranes indicated that a vehicular mechanism was the main proton transport mechanism in all the membranes …”
Section: Resultsmentioning
confidence: 94%
“…As shown in Figure A, it is found that the fuel cell performance of composite membranes exhibited slightly better than pristine SPAEK membrane. The open circuit voltage (OCV) of all fabricated MEAs showed above 0.92 V, indicating that the as‐synthesized membranes had good fuel (H 2 ) permeation resistance . The maximum power densities of SPAEK, SPAEK/SiO 2 , SPAEK/ƒ‐SiO 2 , and Nafion 115 membranes were approximately 296.75, 339.96, 445.34, and 295.99 mW cm −2 under 100% RH, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…This indicates that fuel crossover became significant at 60 °C. The microchannels of the membrane were expanded at high temperatures, and then, the permeability for HCOONa was increased . The presence of HCOONa in the cathode induced the FOR occurring on the Pt surface and thus the mixed potential problem decreasing the cell voltage.…”
Section: Resultsmentioning
confidence: 99%
“…The microchannels of the membrane were expanded at high temperatures, and then, the permeability for HCOONa was increased. 48,49 The presence of HCOONa in the cathode induced the FOR occurring on the Pt surface and thus the mixed potential problem decreasing the cell voltage. Despite of the decrease in the OCV, almost in the whole discharging current density range, the cell voltage was still increased with higher operating temperature.…”
Section: Effect Of the Operating Temperaturementioning
confidence: 99%
“…The water uptake is an important parameter that is related to the ionic conductivity and, consequently, to the fuel cell performance [20][21][22]. These data can be considered as the water uptake at room conditions (temperature and humidity) and are proportional to the functionalization degree.…”
Section: Thermal Stability Of Psumentioning
confidence: 99%